Cover Feature: Chalcogen Bonding with Diaryl Ditellurides: Evidence from Solid State and Solution Studies. (Chem. Eur. J. 25/2022). Issue 25 (12th April 2022) - Weiss, Robin; Aubert, Emmanuel; Groslambert, Loic; Pale, Patrick; Mamane, Victor
Abstract : In the solid state, due to Te⋅⋅⋅ Te interactions, diaryl ditellurides are facing to each other, like these "solid/frozen" Scottish cows in winter. Once the molecules are "defrosted" in solution, new interactions occur with soluble Lewis bases, including some solvents. More information can be found in the Research Article by Patrick Pale, V. Mamane and co‐workers (DOI: 10.1002/chem.202200395 ).